FAKTOR-FAKTOR YANG MEMENGARUHI TRANSFER PRICING - Kabangnga, Cornelita T. R.; Lukman, Hendro (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
That research is aimed to analyze the effect of the effective tax rate, exchange rate, and foreign ownership on transfer pricing in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange period of 2017 – 2021. Method used in this research is a quantitative method utilizing a purposive sampling technique. Valid data is 85 data of 17 companies in the consumer non-cyclicals sector. The collected data were processed using multiple regression analysis and supported by IBM SPSS Statistics version 29 software. The research reveals that effective tax rate and exchange rate have no effect on transfer pricing. Meanwhile, foreign ownership has an effect on transfer pricing. Implication of this research is that there needs to be a balance of ownership so that transfer pricing practices that are carried out are not detrimental to one of the parties and that transfer pricing must be carried out without violating tax regulations in their respective places.